2006
DOI: 10.1523/jneurosci.1401-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Firing Properties of Anatomically Identified Neurons in the Medial Septum of Anesthetized and Unanesthetized Restrained Rats

Abstract: Cholinergic and GABAergic neurons in the medial septum-diagonal band of Broca (MS-DB) project to the hippocampus where they are involved in generating theta rhythmicity. So far, the functional properties of neurochemically identified MS-DB neurons are not fully characterized. In this study, MS-DB neurons recorded in urethane anesthetized rats and in unanesthetized restrained rats were labeled with neurobiotin and processed for immunohistochemistry against glutamic acid decarboxylase (GAD), parvalbumin (PV), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(76 citation statements)
references
References 46 publications
3
73
0
Order By: Relevance
“…The septal region can be divided into the lateral septum, containing mainly GABAergic neurons which coexpress calretinin or calbindin but not parvalbumin (PV) [25], and the medial septum. This contains GABAergic neurons (∼75% of total neurons), some coexpressing PV (∼35%), cholinergic neurons (∼9%) and glutamatergic neurons [26,27]. Both subregions are known to contain spontaneously active neurons, and in the medial septum, PV + GABAergic neurons have been found to be fast spiking [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The septal region can be divided into the lateral septum, containing mainly GABAergic neurons which coexpress calretinin or calbindin but not parvalbumin (PV) [25], and the medial septum. This contains GABAergic neurons (∼75% of total neurons), some coexpressing PV (∼35%), cholinergic neurons (∼9%) and glutamatergic neurons [26,27]. Both subregions are known to contain spontaneously active neurons, and in the medial septum, PV + GABAergic neurons have been found to be fast spiking [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be more accurate to propose that a relationship exists between one structure and that which sets up the hippocampal theta, i.e., the medial septum. Thus, medial septal GABAergic neurons projecting to the hippocampus fire rhythmically at a theta frequency (Borhegyi et al, 2004; Simon et al, 2006) and they set-up theta LFPs there, either directly by activating synaptic currents or resonant properties in postsynaptic cells, or indirectly through interposed local interneurons (Colgin, 2013; Tsanov, 2015). In turn, most hippocampal projection cells, which generate the theta currents, become silent themselves during theta-related behavior, while only a few (place cells) fire transiently at a theta frequency.…”
Section: Common Misconceptions Around Local Field Potentialsmentioning
confidence: 99%
“…Improved amperometric techniques now allow for the measurement of acetylcholine concentrations on faster sub-second timescales and have revealed that acetylcholine concentrations in the cortex can fluctuate rapidly with changes in behavioral state (Parikh et al, 2004, 2007; Burmeister et al, 2008; Mattinson et al, 2011; Howe et al, 2013; Paolone et al, 2013). Although acetylcholine concentrations appear to increase during theta oscillations in the hippocampus of anaesthetized rats, it is not clear whether the increase in hippocampal acetylcholine concentration is accompanied by an increase in firing of medial septal cholinergic neurons (Simon et al, 2006; Zhang et al, 2010, 2011) and whether this is tightly correlated with changes in oscillatory activity during the performance of hippocampal-dependent memory tasks.…”
Section: Volume Vs Wired Transmissionmentioning
confidence: 99%
“…Electrophysiologically, the neuronal cell types populating the medial septum have been classified as slow-firing (~5 Hz) cholinergic, fast- and burst-firing (~10–18 Hz) GABAergic and fast- and cluster-firing (~8–14 Hz) glutamatergic neurons (Griffith and Matthews, 1986; Markram and Segal, 1990b; Jones et al, 1999; Morris et al, 1999; Sotty et al, 2003; Simon et al, 2006; Huh et al, 2010). This classification is consistent with immunohistochemical data and reverse transcription-PCR analysis correlating electrophysiological properties with ChAT, glutamic acid decarboxylase 67 (GAD67) and vesicular glutamate transporters (VGLUT1, VGLUT2) mRNA expression (Sotty et al, 2003).…”
Section: Role Of the Septohippocampal Pathway In Rhythmic Network Oscmentioning
confidence: 99%